Development of recipes and technology for butter cookies using various types of flour and flax seeds - Z. N. Khatko; A. I. Blyagoz; M. K. Bogus; R. Kh. Blyagoz (Новые технологии)
Extension of the assortment of products with increased nutritional and biological value can be achieved in different ways. One way is to use various supplements containing functional ingredients. This approach makes it possible to create food products with specified functional properties. This article presents a developed flour confectionery product, i.e. butter cookies using various types of flour and flax seeds. The characteristics of the chemical composition and functional properties of flax seeds have been presented. The choice of flax seeds as a functional ingredient is due to their high content of biologically active substances, a sufficiently large raw material base and availability. The use of flax seeds in the technology of butter cookies to enrich them with vitamins and minerals has been substantiated. Flax seeds and their processed products have a unique chemical composition, a wide range of properties and a set of biologically active substances. The influence of oatmeal and flaxseed flour on the quality of butter cookies has been studied and their optimal dosages in the cookie recipe selected. The optimal percentage ratio of wheat and oat flour has been established –90:10; wheat and flax flour – 90:10. The influence of flax seed dosage on the quality of butter cookies has been studied and the optimal percentage of flax seeds established – 10%. A recipe and technology for three types of butter cookies have been developed: butter cookies with the addition of flax seeds, butter cookies with the addition of oatmeal and flax seeds, butter cookies with the addition of flax flour and flax seeds.